Comparison of specialist ataxia centres with non-specialist services in terms of care access and organisation, health services resource utilisation and costs in Germany using patient-reported data - Julie Vallortigara; Julie Greenfield; Barry Hunt; Holm Graessner; Carola Reinhard; Andreas Nadke; Bart-Jan Schuman; Deborah Hoffman; Steve Morris; Paola Giunti (Heliyon)
Background: The ataxias are rare complex neurological disorders challenging to diagnose and manage. We explored the patient pathways, health care use and costs of individuals attending a specialist ataxia centre (SAC) compared with non–specialist settings in Germany. Methods: We distributed a survey to people with ataxia to gather information about diagnosis and management of the ataxias, utilisation of health care services, and patients’ satisfaction in both SAC and non-specialist settings. We compared mean resource use and health service costs per patient, stratifying by whether patients attended a SAC or not. Results: We collected and analysed responses from 101 participants. For patients who visited both a SAC and a standard neurology clinic, 67.2 % reported that the care received at a SAC was better. Positive feedback about SAC services included understanding their condition (66.7 % positive feedback), giving practical advice to manage better their ataxia (66.7 % positive feedback) and offering opportunities to take part in research (79.2 % positive feedback). Costs were not significantly different between those attending a SAC and those who did not, although the average cost per patient per year found in SACs was higher compared with non-SACs. The mean total cost per patient over a one-year period was €2091 for non-SAC patients and €4043 for SAC patients (P = 0.19 in adjusted analyses). We identified barriers in accessing SACs including the lack of clear referral pathway and the travel required to such centres. We made recommendations about gaps identified in the care provided based on people's experience and feedback. Conclusions: This study provides useful information about ataxia patient care pathways in Germany, with higher patients’ satisfaction in SAC compared to non-SAC, without a significant difference in costs. The findings can be used to change policy for better care for people with these rare complex neurological diseases.